Safety Climate in the Indonesian Construction Industry: Strengths, Weaknesses, and Influential Demographic Characteristics - Kadir, Abdul; Lestari, Fatma; Sunindijo, Riza Yosia; Erwandi, Dadan; Kusminanti, Yuni; Modjo, Robiana; Widanarko, Baiduri; Ramadhan, Noor Aulia (Buildings (Basel), 2022)
The Indonesian construction industry is a significant contributor to economic growth in Indonesia. However, poor safety performance limits its contributions due to the negative impacts of poor safety on project performance. This research aims to assess the level of the safety climate in the Indonesian construction industry, identify its strengths and weaknesses, and understand the influence of individual demographic characteristics on the safety climate. Data were collected using a questionnaire survey from 1757 respondents working in six large state-owned construction companies in Indonesia. Results indicate that the overall safety climate level is fairly good. However, the safety climate scores of individual safety climate items are observed to vary widely. The scores reveal that construction employees understand the importance of safety and management demonstrates a degree of safety commitment, particularly by having regular safety communications. In contrast, the implementation of safety is limited in reality because safety is not considered a priority at work. Lack of safety resources and limited enforcement of safety rules further hinder the implementation of safety at the project level. Large state-owned construction companies such as those where data were collected should take the lead in changing the work practices in the Indonesian construction industry to improve safety performance. Level of education, length of work experience, position, permanency of job status, work location (project or office-based), and type of project are individual demographic characteristics that influence the level of the safety climate. Understanding the influence of these characteristics on the safety climate allows specific intervention strategies to be used to improve safety.